Assessing Climate Change Challenges and Adaptation Strategies in South Asian Countries: A Review - Giri, Suja; Prasai, Aakriti; Khanal, Ashish; Khamcha, Renuka; Tiwari, Saksham; Khadka, Sharmila; Thapa, Yashodha; Rai, Nitesh; Pantha, Mamata (Journal of Sustainability and Environmental Management, 2023)
The wide range of environmental consequences caused by climate change highlights the urgent need for global action to mitigate its effects, as it poses a significant threat to forest ecosystems, freshwater systems, and the overall stability of our planet. This review paper addresses the limitations in availability of country-specific documents on climate change in South Asian countries and identifies gaps in addressing climate change challenges. By reviewing secondary literature and utilizing online resources, the paper provides insights into the current status of climate change issues and adaptation strategies in Nepal, India, Bangladesh, Bhutan, Pakistan, Afghanistan, Maldives and Sri Lanka. The paper emphasizes the importance of sustainable practices, community involvement, and adaptive management plans in addressing climate change impacts on forests in these countries. It also highlights the need for international collaborations, research, and monitoring to enhance their capacity to mitigate and adapt to climate change. The research findings are valuable for various stakeholders, including ecologists, geologists, hydrologists, local authorities, and governments, as they can be utilized for climate-sensitive planning, project evaluation, integrating gender perspectives, and further research.